Estimation of the collateral circulation index (CCI) in the lower extremities using the impedance rheography and ultrasonic methods - Jerzy WESOŁOWSKI; Andrzej NOWICKI; Barbara TOPOLSKA; Grzegorz PAWLICKI; Leszek FILIPCZYŃSKI; Tadeusz PAŁKO; Henryk RYKOWSKI (Archives of Acoustics, 2015)
In this study values of volumetric blood flow in the thigh, measured using the impedance rheography, were compared with values of volumetric flow in the common femoral artery, measured using the ultrasonic method. We examinated 32 healthy and 46 sick people with occlusion of the pelvic limb arteries. More than 120 measurements were made on these subjects. We ascertained diagnostic usefulness of both methods to simultaneous measurement of blood flow in the peripheral vessels. It seems that association of both of the methods — rheographic and ultrasonic — permits the collateral blood flow to be calculated.